Information and Communications Technology (ICT) based Climate Smart Agriculture (CSA)-Calculator tool for farm level monitoring of performance, synergies and trade-offs - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
To strengthen the quantitative assessment of CSA effect on farm level performance, the tool was adjusted to allow a more generic assessment of farming systems adapting it to the farming characteristics of 8 CSVs (Colombia, Honduras, Nicaragua, Guatemala, Uganda, Nepal, Bangladesh) and included it in the ICT-based CSV monitoring tool.